Does the Use of Lights and Sirens on Ambulances Affect Pre-hospital Time? - Apiratwarakul, Korakot; Lenghong, Kamonwon; Bhudhisawasdi, Vajarabhongsa; Gaysonsiri, Dhanu; Tiamkao, Somsak (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: The use of lights and sirens (L&S) alerts other drivers of the presence of an ambulance and that they are required yield, increasing the speed and safety of emergency medical services (EMS) operations. However, there have been no studies examining the effect of L&S on pre-hospital time conducted in Thai EMS agencies. AIM: The aim of the study was to compare the operation times of ambulances with and without the use of L&S. METHODS: This was a cross-sectional study consisting of patients over 18 years of age assessed and treated through the Srinagarind Hospital EMS between April 2019 and March 2020. Data were collected from the Srinagarind Hospital EMS operation database and hospital information database system. RESULTS: A total of 1764 patients were enrolled, 1426 (80.8%) of whom were transported in an ambulance that used L&S. The mean age of patients in the L&S group was 45.2 ± 6.2 years and 742 (52.0%) were male. The average response times in the L&S and non-L&S groups were 10.2 min and 18.2 min, respectively (p < 0.001). Average L&S transport time was 11.1 min and non-L&S transport time was 17.1 min (p = 0.008). CONCLUSIONS: The use L&S reduced the response and transport times of EMS operations but not affect on-scene time.